Determination of Fleet Performance Through Crew Job Satisfaction at Crude Oil Export Terminal Companies - Ricky Dermawan; Peppy Fachrial; Primadi Candra Susanto (Dinasti Publisher, 2026)
This study was motivated by persistent challenges in maritime human resource management at crude oil export terminal companies, including suboptimal crew management, a lack of transparency in payroll systems, and ineffective compliance management. These issues have negatively affected crew job satisfaction and fleet performance. The study aimed to examine the effects of crew management, payroll systems, and compliance management on fleet performance through crew job satisfaction as a mediating variable at Nembe Crude Oil Terminal Limited, Nigeria. A quantitative research approach with a causal survey design was employed. The study population consisted of 155 crew members working across the company's operational fleet, while the sample was selected using a purposive sampling technique. Primary data were collected through structured questionnaires using a five-point Likert scale and supported by company documentation. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software, including outer model, inner model, and bootstrapping analyses. The findings revealed that crew management, payroll systems, and compliance management each have a positive and significant effect on both crew job satisfaction and fleet performance. Furthermore, crew job satisfaction significantly enhances fleet performance and successfully mediates the relationships between the three independent variables and fleet performance. These findings indicate that improving crew management practices, ensuring transparent and fair payroll systems, and strengthening compliance with international maritime regulations contribute to higher crew job satisfaction, which ultimately enhances operational effectiveness and fleet performance. The study concludes that crew job satisfaction is a strategic factor in improving fleet performance within crude oil export terminal companies. Therefore, management is recommended to strengthen crew management practices, improve payroll transparency and timeliness, and reinforce compliance culture through continuous training and supervision to achieve sustainable operational excellence and long-term fleet performance.